Frailty in old age is associated with decreased interleukin-12/23 production in response to toll-like receptor ligation. - Nathalie Compté; Karim Zouaoui Boudjeltia; Michel Vanhaeverbeek; Sandra De Breucker; Joel Tassignon; Anne Trelcat; Thierry Pepersack; Stanislas Goriely (PLoS ONE, 2013)
Aging is associated with progressive alterations of immune functions, leading to higher susceptibility to bacterial and viral infections and reduced vaccine responses. Data concerning cytokine production in response to Toll-like receptor (TLR) ligands are highly variable in old people, reflecting the heterogeneity of the geriatric population. The aim of our study was to define the relative contribution of age and clinical status on TLR-induced interleukin (IL)-12p70 and IL-23 production as these cytokines play an important role in the protection against intracellular and extracellular pathogens, respectively. For this purpose, we recruited 100 subjects (aged 23-96 years) in the general population or hospitalized for chronic diseases. We collected information on clinical status (medical history, ongoing comorbidities, treatments and geriatric scales), biological parameters (biochemical and hematological tests, telomere length determination, cytomegalovirus serology). Whole blood samples were stimulated with a combination of TLR4 and TLR7/8 ligands. We performed univariate and stepwise backward multivariate analyses regression to define which set of clinical variables could be predictive for IL-12p70 and IL-23 production in these conditions. Our results indicated that age was not correlated with TLR-mediated IL-12p70 and IL-23 production. In contrast, poor nutritional status and frailty in subjects >75 years were associated with decreased IL-12p70 and IL-23 production. By intracytoplasmic staining, we confirmed that production of IL-12/23p40 by conventional dendritic cells (DCs) upon TLR ligation was decreased in frail patients. However, proportion of DCs and monocytes subsets, phenotypic maturation and proximal signaling events were found to be comparable in frail and healthy old subjects. These results suggest the importance of age-associated clinical parameters and not age by itself in the alteration of innate immune responses in old individuals and emphasis the importance of innate immune responses in the susceptibility of frail geriatric patients to infections.